Case Report: CMML in Young Age which Transformed to AML - Wilujeng Anggraini; Herwindo Brahmantyo (Clinical and Research Journal in Internal Medicine, 2023)
CMML (Chronic Myelomonocytic Leukemia) is a rare type of blood cancer that characterized with the presents of monocytes in the blood. 1,2 According to WHO it is categorized as overlapped manifestation of MDS (Myelodysplastic Syndrome) and MPD (Myeloproliferative Disease) or MPN (Myeloproliferative Neoplasm). 2,3 The origin cause of CMML is gene mutation on TET2 (60 %), SRSF2 (50 %), ASLX1 (40 %), and RAS (30 %). 1,3,4 Men are predominantly affected with incidence peak between 71 and 74 years of age, and the prevalence on young adult are very rare and considered to be closely related to the presence of gene mutations in ASLX1. 1,3,5  From several case reports, there were 63 % of CMML patients changed into secondary AML within 1-5 years due to somatic gene mutations in the ASLX1. 2,3,4,6  In this case, we report a 21-year-old male who is diagnosed with CMML and eventually transformed to AML.